Prevalence of comorbidity and its association with demographic and clinical characteristics in persons wearing a prosthesis after a lower-limb amputation - Fred A. de Laat; Pieter U. Dijkstra; Gerardus M. Rommers; Jan H.B. Geertzen; Leo D. Roorda (Medical Journals Sweden, 2018)
Objective: To describe the prevalence of comorbidity and its relationship with demographic and clinical characteristics in persons wearing a prosthesis after lower-limb amputation. Design: Cross-sectional study. Subjects/patients: Persons wearing a prosthesis after lower-limb amputation (n = 171; mean age 65 years (standard deviation 12); 72% men) at the end of outpatient rehabilitation treatment. Methods: Comorbidity was assessed with the Func-tional Comorbidity Index: a list of 18 items addressing the presence of specific comorbid conditions impacting on functional status. Comorbidities in medical records were assessed independently by 2 assessors. Associations with demographic and clinical characteristics were analysed using linear or logistic regression. Results: The median (interquartile range) number of comorbidities was 3 (2; 4). Three or more comorbidities were present in 103 of 171 (60%) participants. Diabetes was present in 71 (41%), cardiac disease in 60 (35%), and lumbago/degenerative disc disease in 39 (23%) participants. The prevalence of comorbidities was higher in women and those with vascular cause of amputation. Conclusion: There is a high prevalence of comorbidity at the end of outpatient rehabilitation treatment in persons wearing a prosthesis after a lower-limb amputation, especially in women and those with vascular cause of amputation.